(untitled) (Global Journal of Science Frontier Research, 2025)
Nine varieties of maize (Zea mays L.) namely H4226, RAJAJI, TMMH826, TATA 849, KAVERI 25K-60, RMH 1818, KANAK, BISCO-940 and RASI 4640 were evaluated on thirteen parameters in a randomized block design with three replications. The objectives of the experiment were to select suitable plant types based on considering all the thirteen parameters, suggesting scope for further improvement and recommending suitable maize ideotypes for cultivation by farmers of this region. Normalized cumulative ranks analysis found BISCO-940, KAVERI 25K-60, H4226, TATA 849 and TMMH826 to be top five varieties that could be recommended to farmers for cultivation on the criteria of less number of leaves per plant, small and narrow leaves with high venation, early tasseling and silking, dwarf plant types with lower cob placement, long cobs with less number of bracts for ease of peeling off the cobs and thick cobs with more kernels and kernel rows.